Social cohesion in Latin America : concepts, frames of reference and indicators (UN ECLAC SantiagoCL)
Describes the main results of the project titled "Measuring social cohesion in Latin America." Attempts to strengthen the conceptual framework that ECLAC has developed for understanding and measuring social cohesion, and to encourage the incorporation of the issue on the region's national agendas.
Keywords: SOCIAL INTEGRATION